Salinity tolerance of some elite rice breeding lines at reproductive stage (Bangladesh Rice Journal, 2015)
Rice is relatively sensitive to salinity at reproductive stage. Screening of rice cultivars for salt tolerance at the reproductive stage is difficult at field conditions because of the heterogeneity of soil salinity. The present investigation aimed to characterize reproductive growth and yield potential of elite breeding lines in controlled saline environment at net house conditions. The experiment involved three advanced breeding lines, BR7100-R-6-6, IR78794-B-Sal29-1 and IR59418-7B-21-3 and a salt-tolerant check (BRRI dhan47) and susceptible check (BRRI dhan28) under four salinity levels (0, 4, 8, and 12 dS/m) at reproductive stage. The factorial experiment was conducted in randomized complete block design with three replications. Salinity × genotypes demonstrated significant interactions on some yield contributing characters and grain yield. Salinity stresses, at 8 and 12 dS/m, decreased plant height, tiller and panicle numbers, panicle length, filled grain number and grain yields of all the tested genotypes in different magnitude. The breeding line IR59418-7B-21-3 performed greater tolerance to salinity than other tested lines and check varieties. At 8 dS/m IR59418-7B-21-3 produced 72% relative grain yield compared to that of 31% in BRRI dhan47. The breeding lines, BR7100-R-6-6 and IR78794-B-Sal29-1 produced 40 and 59% relative grain yield respectively, at 8 dS/m. At 12 dS/m, all the tested genotypes produced less than 20% relative grain yield. Based on the salinity pressure (8 dS/m) at the reproductive stage, IR59418-7B-21-3 produced 68% higher yield than that of BRRI dhan47. BR7100-R-6-6 and IR78794-B-Sal29-1 out yielded BRRI dhan47 by 45 and 49% respectively. All the three breeding lines performed better than that of BRRI dhan47 in terms of salinity tolerance at the reproductive stage.Bangladesh Rice j. 2014, 18(1&2): 33-37